PENGEMBANGAN BISNIS AGROWISATA BUAH NAGA DI KOTA BATAM MELALUI PENDEKATAN DESIGN THINKING MANAGEMENT - Jurnal Ilmiah Manajemen UPB (Universitas Putera Batam, 2017)
The competitions of robust businesses nowadays have caused and influenced employers to be cautious in viewing the business opportunities that will be established as well as choosing the right sector to be a place of business. One of businesses having promisingly good prospects is agro-tourism (agribusiness). This study aims to develop and manage business innovation of agro-tourism (a case study of ZORE) by using Design Thinking Approach. In the process, there are five-steps of design thinking management being applied, i.e. empathize, define, ideate, prototype, and test, where the five steps are basically promoting human center approach in the thought process that focuses on human beings themselves (customer orientation) as a focus of innovation and supported with the prototype, the resulting innovation can be a product, service or business design. The formulation strategy of the ZORE agro-tourism business development based on the study, namely continuous and sustainable development, supports of relevant stakeholder, dissemination of information related to business excellences, and stakeholder dialogue for sustainable agro-tourism.